Is the indocyanine green clearance test useful in viral acute liver failure? Maybe! : ICG-PDR in viral acute liver failure - Zanini, Victor; Vetrugno, Luigi; Ventin, Marco; Cherchi, Vittorio; Lugano, Manuela; Baccarani, Umberto; Bove, Tiziana (Acta Biomedica Atenei Parmensis, 2022)
N/A